Analisis Penerapan No First Use Policy Dalam Penggunaan Senjata Nuklir: Sebuah Tinjauan Yuridis - Yunia Utami Indah Haloho; Xavier Nugraha; Atiqoh Farhan Maulani (JURNAL ILMIAH LIVING LAW, 2020)
The preservation of the stability of world peace became one of the wishes of the entire international community. But these expectations seemed to be a sense of concern in the event of a war between countries using nuclear weapons. International law governs the nuclear weapons of international treaties, one of which is the Treaty on Non-Proliferation of Nuclear Weapons in 1968. In addition to providing a guarantee of a sense of security was formed No First Use Policy to ensure the country owners of nuclear weapons are not the first party to use nuclear weapons in the event of a conflict with other countries. The purpose of this research is to learn about the implementation of No First Use Policy on the use of nuclear weapons by the countries that have them and the international security of the world. The method used in the study is normative juridical is supported by data obtained by library research. Regarding the implementation of the No First Use Policy each country with nuclear weapons has different attitudes about it. Whereas No First Use Policy has had a positive impact on the arrangement of the use of nuclear weapons of the world for security and order.